Analysis of Money Supply and Inflation as Well as Trade Balance on Exchange Rates in Indonesia Using BI Rate as A Moderating Variable - Bagaswara, Muhammad Rifki Aksan; Priyagus, Priyagus; Lestari, Diana (CV. Publikasi Indonesia, 2025)
The purpose of this study is to find out the Analysis of the Money Supply and Inflation and Trade Balance to the Exchange Rate in Indonesia Using the BI Rate as a Moderating Variable. This study uses data from the time sequence of 2005-2023 using secondary data, using Multiple Linear Regression and Moderating Variable analysis tools with the help of SPSS 23.0 software, to use BI Rate as a Moderating Variable to provide a strengthening or weakening relationship between Inflation to Exchange Rate and to determine the relationship between variables such as Money Supply, Inflation, Trade Balance and BI Rate to Exchange Rate. Based on the results of this study, it shows that the Money Supply has a positive and significant effect on the Exchange Rate in Indonesia, Inflation also has a negative and insignificant effect on the Exchange Rate in Indonesia, the Trade Balance has a negative and significant effect on the Exchange Rate in Indonesia, but the BI Rate is not a moderating variable because it cannot strengthen the relationship between Inflation and the Exchange Rate in Indonesia.